Advancements in retrofitting reinforced concrete structures by the use of CFRP materials - Sena-Cruz, José (2014)
Reinforced concrete is nowadays one of the major structural materials used in infrastructures’ construction. As the years passed since the beginning of its use, technology has changed and today it is known that a large number of constructions do not verify some of the most recent safety requirements in addition to the durability problems that several structures face. This calls for the need for corrections and/or strengthening activities. Fibre reinforced polymer materials (FRP) have been used in Civil Engineering applications due to: lightweight, good mechanical properties (stiffness and strength), corrosion-resistant, good fatigue behaviour, easy application and virtually endless variety of shapes available. Recent advancements in retrofitting reinforced concrete structures by the use of CFRP materials promoted by the authors of the present chapter are herein summarized. Firstly a brief overview on the most common properties of old reinforced concrete constructions those who might need for interventions, is presented. Then, the most common repairing and/or strengthening techniques are addressed. Finally, a deeper look is taken on the new repairing and/or strengthening techniques using FRP reinforcements.